Chemical evolution and evaporation of shallow groundwaters discharging from a gold mine, southern New Zealand. (November 2020) - Weightman, Erin; Craw, Dave; Rufaut, Cathy; Kerr, Gemma; Scott, James
Abstract: Waste rock piles at the Macraes gold mine in southern New Zealand expose abundant fresh schist to alteration reactions that principally involve pyrite, chlorite, and calcite, yielding alkaline waters (pH~8) with elevated dissolved loads. Pyrite oxidation has resulted in dissolved sulfate concentrations rising up to ~3000 mg/L over 10 years, and this high sulfate is a potential environmental issue in waters leaving the site. Up to 600 mg/L dissolved Mg 2+ results from chlorite dissolution. The site has a semi-arid climate and evaporative precipitation of sulfate minerals could contribute to an engineered water treatment system. However, the evolved waters are saturated or supersaturated with respect to carbonate minerals and spontaneous precipitation of aragonite is widespread, thereby limiting Ca-sulfate (gypsum) precipitation. Localised precipitation of Mg-sulfate (epsomite) also occurs, but this redissolves during rain events. Compositionally different waters seeping from the mine tailings impoundment have >2500 mg/L dissolved sulfate, and elevated Na +, K + and Cl − from addition of reagents in the processing system. These seepage waters have also undergone interaction with waste rocks in the impoundment walls. The seep waters are approximately saturated with respect to carbonate minerals, but no spontaneous carbonate precipitation has occurred over two years of observations. Ephemeral evaporative epsomite and Na–Mg sulfate (bloedite) precipitates form locally. Geochemical modelling suggests that evaporative precipitation of gypsum has potential to remove sulfate from both types of water, especially if carbonate precipitation was suppressed by lowering the water pH to ~6 in an engineered treatment system that involves substantial evaporation. Graphical abstract: Image 1 Highlights: Mine waste rock waters have dissolved sulfate up to 3000 mg/L from pyrite. Calcite and chlorite dissolution yield alkaline pH and high dissolved Mg. Precipitation of aragonite inhibits gypsum precipitation and lowering of sulfate. Waters precipitate Mg-sulfate after substantial evaporation. Evaporative sulfate removal is enhanced at lower pH.